Investigating the Effect of Deictic Movements of a Multi-Robot. Issue 3 (7th February 2021) - Lee, Ahreum; Jo, Wonse; Kannan, Shyam Sundar; Min, Byung-Cheol
ABSTRACT: While research on human-robot interaction is ongoing as robots become more readily available and easier to use, the study of interactions between a human and a team of multiple robots represents a relatively new field of research. In particular, how multi-robots could be used for everyday users and how the characteristics of multi-robots would affect human perception and cognition has not been explored. In this paper, we specifically focus on physical affordances generated by the movements of multi-robots, and investigate the effects of deictic movements of multi-robots on information retrieval by conducting a delayed free recall task. We conclude with further discussion of how the movements of the multi-robot reshape the way of people perceiving information and what should be considered to design a multi-robot-based display.